2010
DOI: 10.1039/b9nj00771g
|View full text |Cite
|
Sign up to set email alerts
|

The influence of electron delocalization upon the stability and structure of potential N-heterocyclic carbene precursors with 1,3-diaryl-imidazolidine-4,5-dione skeletons

Abstract: (2010). The influence of electron delocalization upon the stability and structure of potential N-heterocyclic carbene precursors with 1,3-diaryl-imidazolidine-4,5-dione skeletons. New Journal of Chemistry, 34 (7), 1295-1308. doi:10.1039 Aiming to develop synthetic protocols for the preparation of N-heterocyclic carbenes (NHCs) with increased π-acceptor character featuring N-pentafluorophenyl substituents, the molecular 2-chloro-1,3-bis(pentafluorophenyl)imidazolidine-4,5-dione (1a) was isolated from the conden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 80 publications
0
33
0
Order By: Relevance
“…1.40 in benzene), [25] in agreement with the extensive electron delocalization over the N À C À N and C À C À C fragments of the framework. The N(1) À C(4) and N(2) À C(2) bonds (1.476(3) and 1.487(3) , respectively) are very long for amide functionalities, and much longer than the corresponding distances observed in the molecular derivatives H (1.348(5)-1.381(2) ) [19] or in hexamethylmalonamide (1.34 ). [26] As observed in the precursor to K, [20] the competitive delocalization over the C À C À C backbone in 1 a-d reduces the multiple-bond character of the amidic C À N bond.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…1.40 in benzene), [25] in agreement with the extensive electron delocalization over the N À C À N and C À C À C fragments of the framework. The N(1) À C(4) and N(2) À C(2) bonds (1.476(3) and 1.487(3) , respectively) are very long for amide functionalities, and much longer than the corresponding distances observed in the molecular derivatives H (1.348(5)-1.381(2) ) [19] or in hexamethylmalonamide (1.34 ). [26] As observed in the precursor to K, [20] the competitive delocalization over the C À C À C backbone in 1 a-d reduces the multiple-bond character of the amidic C À N bond.…”
Section: Resultsmentioning
confidence: 96%
“…We have shown that the [3+2] ring-closing reactions of easily accessible nonfluorinated as well as poorly nucleophilic, fluorinated, and perfluorinated N,N-bisA C H T U N G T R E N N U N G (phenyl)formamidines [18] with highly electrophilic oxalyl chloride proceeds readily to give molecular products H instead of the expected ionic derivatives I. [19] These molecular products H displayed reactivity typical of alkyl halides, and in our hands failed to generate the targeted NHCs, J. Computational analyses showed that the oxalamide backbone significantly lowered the energy of the LUMO of the desired carbenes J, increasing their p-acceptor (electrophilic) character and decreasing their stability to the point where it rendered them too instable for isolation. Meanwhile, a series of closely related amido and diamidocarbenes have been isolated or incorporated in transition-metal complexes, including the anionic carbenes K, [20] the neutral derivatives L, [21] and the five-membered monoamidocarbenes M. [22] Although carbenes K-M are highly reactive compounds, it is clear that the destabilizing influence of the amido functionalities on the amidocarbene moiety in these compounds is inferior in magnitude to that observed in the oxalamide ligands J.…”
Section: [Rha C H T U N G T R E N N U N G (Cod)a C H T U N G T R E N mentioning
confidence: 97%
See 1 more Smart Citation
“…Only few such examples have been structurally characterized to date, 17 and we propose that the competitive delocalization of the nitrogen lone pairs onto the exocyclic amidine moieties is responsible for a reduced stabilization of the carbene structure. 18 In support of this theory, the two C-N bonds of each pendant amidine group in 2 are almost equal in length. Treatment with potassium hexamethyldisilazide in toluene yielded nevertheless the NHC complex 3, with nickel retaining the chloride in its coordination sphere.…”
mentioning
confidence: 83%
“…Although they are typically known for their exceptional σ-donor abilities [5], π-interactions play a role in the bonding between NHCs and transition metals, as indicated by recent studies [6][7][8][9][10][11]. Hobbs and coworkers focused on preparing NHCs with reduced-energy lowest unoccupied molecular orbitals (LUMOs) to determine the importance of π-interactions between carbenes and transition metals [12]. By introducing an oxalamide into the heterocyclic backbone (e.g., 2 in Scheme 1), they discovered that the resulting carbene, referred to as N,N′-diamidocarbene (NAC), possessed a higher electrophilicity compared with typical NHCs.…”
Section: Introductionmentioning
confidence: 98%